Clinical and radiographic comparison of primary molar pulpotomy using formocresol, portland cement, and NeoMTA plus: a randomized controlled clinical trial - Elham Farokh Gisour; Fatemeh Jahanimoghadam; Pouya Karimipour (Scientific Reports)
Abstract The present study aimed to compare the clinical and radiographic success rates of Formocresol (FC), Portland Cement (PC), and NeoMTA Plus in primary molar pulpotomy. Ninety-six primary molars in ninety-six children aged 3‒9 years were randomly assigned to FC, PC, and NeoMTA Plus groups. Radiographic and clinical follow-up evaluations were performed at six and twelve months. After six and twelve months, clinical success rates were 100% in the three groups. The radiographic success rates in the 6-month follow-up were 96.7 and 96.7% in the FC and PC groups and 100% in the NeoMTA Plus group. At 12 months, radiographic success rate was 93.8, and 93.8% in the FC and PC groups and 96.9% in the NeoMTA Plus group. There were no significant differences between the three groups at all follow-up evaluations. NeoMTA Plus showed highest success rate, clinically and radiographically. PC and NeoMTA Plus can be considered as an alternative to FC.